E-Learning Process in Elementry School: Bibliometrics Approach - Elihami Elihami (Universitas Muhammadiyah Enrekang, 2022)
In the transition to entirely online learning for Covid-19, the learning management system (LMS) plays a critical role in higher educational institutions around the world. The Nvivo plus 12 system and the Vosviewer program were utilized in the qualitative research. The goal of this research paper is to look into the e-learning process among students who are familiar with the internet. The development of an online education model (Zoom, WA, LMS), platform, and comprehensive online e-Learning would have a big impact. Full e-learning is a term used to describe fully online learning that occurs between traditional campus education and online learning (e-learning) that occurs outside of the campus facing covid-19. The use of a virtual learning management system (LMS) allowed for the promotion of online learning (e-learning). The new research on virtual Learning management systems has the potential to transform essential components of classrooms by utilizing forms that can have a substantial impact on teaching and learning. According to the findings, technology affects librarians' perspectives of their jobs, students' needs, and faculties that might help them develop. In order to produce a selection and motivate pupils to think about it, full e-learning must collaborate with them. Despite the fact that comprehensive e-learning is becoming a viable strategy for various institutions in the country, some universities, particularly in developing countries, are opposing the transition.